2016
DOI: 10.5604/01.3001.0009.9717
|View full text |Cite
|
Sign up to set email alerts
|

Tell el-Farkha. Excavations, 2012–2013

Abstract: Excavations at Tell el-Farkha in 2012 and 2013 were conducted on all three koms making up the site. The upper layers excavated on the Western Kom during the first campaign were connected with the beginning of phase 4 at Tell el-Farkha and the lower layers with phase 3. A few poorly preserved rooms were unearthed, mainly in the southern part of the trench. Also part of a brewery dated to Naqada IIIA1 was explored. A rectangular building with thick walls discovered on the Central Kom was most probably the remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
0
3
0
4
Order By: Relevance
“…La edificación, de anchas paredes y diversos compartimentos en los que también se registra una clara delimitación de actividades (Chłodnicki y Ciałowicz, 2013), pudo haber tenido funciones de índole tanto residencial como administrativa, dados los numerosos hallazgos en su interior que comprenden tokens y fragmentos de sellos de arcilla, así como cerámicas procedentes del Levante (Czarnowicz, 2012;Kołodziejczyk, 2012). Luego de su destrucción (ver más abajo), se erigió en ese lugar otro complejo de grandes dimensiones y con múltiples recintos en su interior, entre los que se destacan dos capillas con sendos depósitos votivos, que ha sido interpretado como un "centro cúltico-administrativo" (Ciałowicz, 2012a), asociado a la élite local de la época posterior (Chłodnicki, 2012). ISSN 0325-1209…”
Section: Especialización Funcionalunclassified
See 1 more Smart Citation
“…La edificación, de anchas paredes y diversos compartimentos en los que también se registra una clara delimitación de actividades (Chłodnicki y Ciałowicz, 2013), pudo haber tenido funciones de índole tanto residencial como administrativa, dados los numerosos hallazgos en su interior que comprenden tokens y fragmentos de sellos de arcilla, así como cerámicas procedentes del Levante (Czarnowicz, 2012;Kołodziejczyk, 2012). Luego de su destrucción (ver más abajo), se erigió en ese lugar otro complejo de grandes dimensiones y con múltiples recintos en su interior, entre los que se destacan dos capillas con sendos depósitos votivos, que ha sido interpretado como un "centro cúltico-administrativo" (Ciałowicz, 2012a), asociado a la élite local de la época posterior (Chłodnicki, 2012). ISSN 0325-1209…”
Section: Especialización Funcionalunclassified
“…La división del trabajo también es atestiguada a través de la existencia de actividades artesanales y de aprovisionamiento de materias primas y bienes suntuarios manufacturados procedentes del exterior. Tanto la elaboración de objetos producidos a partir de diversas materias primas exógenas -entre los que sobresalen dos estatuillas laminadas en oro con incrustaciones de lapislázuli en los ojos 10 (Nagada IIIB) (Ciałowicz, 2012b) y un conjunto de pequeñas figuras de marfil y hueso colocadas en los depósitos votivos del "centro cúlticoadministrativo" y en el ajuar de la Tumba 24 (Kurzyk, 2012;Ciałowicz, 2011a)-como la industria lítica (Chłodnicki, 2012;Pryc, 2012), la producción de objetos en piedra -por ej., vasos y cuentas-(Jórdeczka y Mrozek-Wysocka, 2012) y la producción cerámica tanto de uso doméstico como ritual (Ciałowicz, 2012a), demuestran un elevado nivel de especialización artesanal. Por su parte, la considerable presencia de bienes importados desde el Levante -entre los que se destacan los objetos de cobre así como jarras que debieron contener aceite de oliva y vino (ver Czarnowicz, 2012)-apuntan a la posible existencia de especialistas encargados de realizar y controlar los intercambios con esa región (ver Daizo, 2019).…”
Section: Dossierunclassified
“…During Polish research a lot of important discoveries have been made (see, e.g., Chłodnicki et al, 2012). It is enough to mention the big buildings from the time of the Lower Egyptian culture and monumental Naqadian magazines on the Central Kom, the oldest brewery centre in the Nile Delta, the huge Naqadian buildings and Early Dynastic cultic-administrative centre with two votive deposits on the Western Kom, as well as golden figurines representing a Predynastic ruler, a monumental mastaba and a cemetery on the Eastern Kom.…”
mentioning
confidence: 99%
“…showed that the overwhelming majority were of light chert (84.09%) ( (Chłodnicki et al 2012;Ciałowicz 2007). The possibility that the piece was an heirloom cannot be ruled out, but the lesser quality of that particular piece (the ripple-flakes did not carry all the way across the face and join in the middle), combined with the unusual dark raw material could be an indication that it was a later example made after the knowledge and skill of such production was not in regular practice.…”
Section: Ripple-flaked Knivesmentioning
confidence: 99%
“…Those ritual contexts included burials, where they were primarily found, and a cache of goods at the Tel el-Farkha settlement, which also included two golden statues and an over-sized bifacial knife (Ciałowicz 2012;Kabacinski 2012). One possible RFK was also found in a domestic context.…”
Section: Ripple-flaked Knivesmentioning
confidence: 99%